Evidence of reflected internal solitary waves in the Strait of Gibraltar. - Roustan, Jean-Baptiste; Bordois, Lucie; García-Lafuente, Jesús; Dumas, Frank; Auclair, Francis; Carton, Xavier (American Geophysical Union, 2024)
Large‐amplitude internal solitary waves (ISWs) propagating eastward toward the Alboran Sea have long been known in the Strait of Gibraltar. New in‐situ data and satellite images evidence northwestward propagating ISWs. These waves are probably the reflection of the well‐known eastward propagating wave along the Moroccan shelf. A simple 2D‐vertical section, run with the compressible non‐hydrostatic Coastal and Regional Ocean COmmunity model, illustrates that the Moroccan slope is conducive to reflection of incident solitary waves of amplitude observed in the Strait of Gibraltar. A clear signature of these waves in the Tarifa high‐frequency sea level oscillations is depicted that paves the way to studies of the seasonality of ISWs in the Strait of Gibraltar with the long‐time series of sea level at Tarifa. The polarity of the reflected waves, observed with Acoustic Doppler Current Profilers/Conductivity‐Temperature‐Depth array moorings, presents a slight variability possibly due to the internal tide oscillations. The reflected ISWs arrives at the mooring location in phase with the peak of the internal tide. For the strongest tide, the pynocline approaches a critical point where the polarity of the ISWs might reverse.
Keywords: Oceanografía fisica; Oleaje; Hidrodinámica; Gibraltar (Estrecho); Strait of Gibraltar; Sea level; Reflected waves; Internal waves